An Analogical Approach to Colors and Symbolism in Romanian and Turkish Folk Art - Özlem Kaya; Sinziana Romanescu (Art-Sanat)
Folk art is defined as creation that does not belong to the classical or modern arts but is generally included in traditional or domestic handcraft production. Works of folk art are generally of anonymous origin; their producers have not graduated from aesthetic or artistic studies in the narrowest sense. The discovery of the phenomenon of folk art as a valuable part of culture is due to the development of the science of art history at the end of the 19th century. From the aesthetic and historical point of view, it occurred in parallel with the gradual disappearance of this phenomenon in the European societies that were in the process of industrialization. At the end of the 19th century, with the gradual disappearance of handicraft traditions in Central and Western Europe and later in Eastern Europe, folk art lost its original foundation. Due to theories of primitivism, popular art was given special attention during this period by - and thanks to -artists of the modernist trend. During this period, folk clothes and clothing motifs were seen frequently. In particular, various pictures, colors, symbols, lines and images representing flowers were used quite often. What the grounds for all these people are, their importance, their depth, why they are repeated and how they are repetitive patterns are hidden in these clothes and works. Preservation of the national culture and the local folklore is very important and we think, first and foremost, that we should understand the significance of these symbols and colors that represent our heritage. The aim of this study is to analyze colors and symbols in Romanian and Turkish Folk Art with an analogical approach. In this study, examples of colors and symbols in Romanian and Turkish Folk Art were examined from areas such as clothing, weaving and ceramics and the use of symbols, the meanings of colors were conveyed and supported by patterns and it was concluded that there were similarities as well as regional differences between the two countries.